Effects of personalized cosmetics on basic skin parameters monitored by non-invasive biophysical measurements - Emeti Vidović, Ana; Ivetić, Zorana; Stanivuković, Aleksandra; Terzić, Dejan (Archives of Pharmacy, 2022)
Personalized skincare approach represents actively growing area in cosmetics industry. Main advantage of personalized cosmetics is a possibility to choose ingredients according to in vivo measurements and monitoring of skin parameters. The aim of this study was to evaluate efficacy of personalized creams. Study included 90 healthy subjects, average age 35.1±12.8 years, 78 (86%) females and 12 (13.3%) males with dominantly dehydrated skin (n=54, 60%). Multi Probe Adapter (Courage & Khazaka, Germany) was used for facial skin parameters analysis: hydration, surface sebum content, erythema/melanin index and skin pH at forehead, chin and cheeks. Measurements were performed twice under controlled conditions, before and after personalized creams application. Subjects have used personalized creams twice a day during three months. Hydration was significantly increased (41.4±12.5 to 53.1±11.1; p